ANALISIS PENGGUNAAN CAMPUR KODE MAHASISWA MELALUI PESAN WHATSAPP DAN SUREL SEBAGAI IMPLIKASI DARI XENOGLOSOFILIA [ANALYSIS ON STUDENTS' CODE-MIXING USAGE THROUGH WHATSAPP MESSAGE AND EMAIL AS AN IMPLICATION OF XENOGLOSSOPHILIA] - Sitorus, Jonter Pandapotan (Polyglot, 2025)
Language contact is one of the reasons for one's language variety or variation. The use of variation will also depend on the language attitude, whether it is included in a positive or negative language attitude toward a language. One of the languages in question is Indonesian, which is often mixed with words from foreign languages, especially English, thus violating the language codes of the variety used. This is known as code mixing. This study uses a survey method to find out the language attitudes of students at one of the private universities in Tangerang towards Indonesian and an observation method through the Simak Libat Cakap (SLC) technique to analyze the forms of student code-mixing. Based on the study's results, students still maintain a positive attitude towards the language, as evidenced by their pride in the Indonesian language. The findings of code mix used, such as the words text, quiz, error, submit, online class, upload, join, and others. Thus, from the results of the analysis of the forms of student code mix, it is evident that the phenomenon of xenoglossophilia occurs. Abstrak Bahasa Indonesia Kontak bahasa menjadi salah satu alasan terjadinya ragam atau variasi bahasa seseorang. Penggunaan variasi itu pun akan bergantung pada sikap berbahasanya apakah termasuk dalam sikap bahasa positif atau negatif pada suatu bahasa. Salah satu bahasa yang dimaksud adalah bahasa Indonesia yang kerap kali dicampuradukkan dengan kata-kata dari bahasa asing sehingga menyalahi kode-kode bahasa dari ragam yang digunakan. Hal inilah yang dikenal dengan istilah campur kode. Penelitian ini menggunakan metode survei untuk mengetahui sikap bahasa mahasiswa UPH terhadap bahasa Indonesia dan metode observasi melalui teknik Simak Libat Cakap (SLC) untuk menganalisis bentuk-bentuk campur kode mahasiswa UPH. Berdasarkan hasil penelitian, mahasiswa UPH tergolong memiliki sikap bahasa positif berupa sikap bangga terhadap bahasa Indonesia. Akan tetapi, dari hasil analisis bentuk-bentuk campur kode mahasiswa UPH, mengimplikasikan bahwa fenomena xenoglosofilia benar-benar terjadi.